Diversity, distribution, and conservation status of Betta fish (Teleostei: Osphronemidae) in Aceh waters, Indonesia. Issue 1 (31st December 2022) - Nur, F. M.; Batubara, A. S.; Fadli, N.; Rizal, S.; Siti-Azizah, M. N.; Muchlisin, Z. A.
Abstract: The Betta broodfish supply in Indonesia majorly comes from wild populations and fetches a higher price compared to hatchery cross-breeds, especially Betta rubra . This condition exerts pressure on the wild populations. Therefore, this study aims to examine the diversity, distribution, and conservation status of Betta fish species list in the study area. A total of 422 Betta fishes were collected from January 2019 to January 2021 from 19 of 59 sampling locations surveyed, consisting of four species, namely, Betta imbellis (TL: 14.09–31.98 mm; BW: 0.03–0.39 g), B. splendens (TL: 21.09–40.14 mm; BW: 0.05–0.70 g), B. rubra (TL: 11.35 to 47.80 mm; BW: 0.02–0.90 g), and B. dennisyongi (TL: 20.09–47.81 mm; BW: 0.07–0.91 g). There are four Betta species occurred in Aceh waters, namely B. dennisyongi, B. rubra, B. splendens, and B. imbellis . The results showed that B. dennisyongi was found at 8 sampling locations and had higher local distribution (13.56% LD) followed by B. rubra (8.47% LD), B. splendens (6.78% LD) and B. imbellis which had the lowest distribution and was only found in two locations (3.39% LD). Furthermore, field measurements (in situ) of water quality in the wild habitat showed temperature ranging from 23.7 to 31.9°C while pH ranged from 5.24 to 8.51. Based on the IUCN Redlist data, B. rubra is categorized as being critically endangered.